Multi-faceted approach to radicalization in terrorist organizations - Bal, Ihsan; Ozeren, Suleyman; Sozer, Mehmet Alper (NATO science for peace and security series. E, Human and societal dynamics, 2011)
Terrorism, and the radicalization of terrorists in particular, has become a focus for academics and practitioners in recent years. However, the concept of radicalization has a variety of definitions and this is due in part to its relationship to other concepts with no clearly agreed definition, such as terrorism. Clarifying the intellectual background is important if the various trends in radicalization are to be properly understood. A clear picture of such trends is essential for the analysis of the radicalization process which will enable law enforcement agencies, academics and policymakers to develop tactics and strategies to counter such radicalization. This book presents the proceedings of the NATO 2010 Advanced Research Workshop on Developing Prevention Strategies and Tactics in Countering Radicalization, held in Antalya, Turkey, in December 2010. This workshop reviewed the process through which an individual becomes radicalized, examining the concept of radicalization and presenting comparative perspectives from different countries. It sought to propose a model of prevention policy to target radicalization and present the fundamental dynamics of preventing radicalization. Topics addressed include militant identity building procedure, how radicalization is financed and preventive strategies to counter the use of sophisticated weapons. The book is an important addition to the field of countering terrorism and will be of interest to all practitioners, academics and policymakers involved in this endeavor.